A hierarchical scaffold with a highly pore-interconnective 3D printed PLGA/n-HA framework and an extracellular matrix like gelatin network filler for bone regeneration. Issue 22 (21st May 2021) - Dou, Yichen; Huang, Jinhui; Xia, Xue; Wei, Jiawei; Zou, Qin; Zuo, Yi; Li, Jidong; Li, Yubao
Abstract : The ideal scaffold for bone repair should have a hierarchical pore structure and gradient degradation performance to satisfy the uniform adhesion and proliferation of cells in the scaffold at the early stage of implantation, as well as providing space for the subsequent regeneration of bone tissue. Abstract : The ideal scaffold for bone repair should have a hierarchical pore structure and gradient degradation performance to satisfy the uniform adhesion and proliferation of cells in the scaffold at the early stage of implantation, as well as providing space for the subsequent regeneration of bone tissue. To this end, we developed a hierarchical polylactic acid glycolic acid copolymer (PLGA)/nano-hydroxyapatite (n-HA)/gelatin (Gel) (PHG) scaffold with a printed PLGA/n-HA (PH) framework and a Gel network filler for bone regeneration by the combination of 3D printing and freeze-drying technologies. The fabricated PHG scaffold features large front hole size (>1100 μm × 1100 μm) and side hole size (>500 μm) to provide sufficient open space and reliable integrated support for cell and tissue ingrowth. The gelatin network filled in the PH framework played the role of a cell holder just like an extracellular matrix (ECM) in the early stage. In vitro degradation experiments revealed that the gelatin network completely degraded within 5 weeks while the structural integrity of the framework still remained at the 32nd week. The results of cell culture confirmed that the PHG scaffold was more conducive to cell attachment. In vivo assessments in a rat femoral defect model showed that PHG scaffolds were more favored for new bone formation and achieving a tighter bond between the scaffold and the original tissues. The hierarchical PHG scaffold has great application potential in bone tissue engineering and will provide a reference for the model design of bone scaffolds.